Umbilical cord-care practices in low- and middle-income countries: a systematic review. Issue 1 (December 2017) - Coffey, Patricia; Brown, Siobhan
Abstract Background Neonatal sepsis is the third leading cause of deaths for infants in their first month of life. The newly cut umbilical cord can be a pathway for bacteria that can cause newborn sepsis and death. Optimal umbilical cord care practices for newborns and during the first week of life, especially in settings with poor hygiene, has the potential to avoid these preventable neonatal deaths. The purpose of this review of cord care practices is to assist in the development of behavior-change strategies to support introduction of novel cord-care regimens, particularly 7.1% chlorhexidine digluconate for umbilical cord care. Methods We searched domestic and international databases for articles that were published in English between January 1, 2000, and August 24, 2016. We found 321 articles and reviewed 65 full-text articles using standardized inclusion criteria. The primary criteria for inclusion was a description of substances applied to the umbilical cord stump in the days following birth. Results We included 46 articles in this review of umbilical cord-care practices. Articles included data from 15 low- and middle-income countries in sub-Saharan Africa (8 countries), Asia (5 countries), North Africa (1 country), and Latin America and the Caribbean (1 country). Findings from this review suggest that documentation of cord-care practices is not consistent throughout low- and middle-income countries, yet existing literature depicts a firm tradition of umbilical cord care in every culture. Cord-care practices vary by country and by regions or cultural groups within a country and employ a wide range of substances. The desire to promote healing and hasten cord separation are the underlying beliefs related to application of substances to the umbilical cord. The frequency of application of the substance (either the number of days or the number of times per day the substance was applied), and source and cost of products used is not well-characterized. Conclusions This desire to actively care for the umbilical cord of a newborn—as noted in the variety of cord care practices and beliefs identified in this review—points toward the need to contextualize any behavior change approach to align with the local culture.